2019
DOI: 10.1016/j.chiabu.2019.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Childhood poly-victimization and children’s health: A nationally representative study

Abstract: Background: Although research on the negative effects of childhood poly-victimization is substantial, few studies have examined the relationship between poly-victimization and younger children's physical health and diseases.Objective: This study examines the effects of poly-victimization on children's health problems requiring medical attention. Methods:We collected data with a self-report questionnaire from a national proportionately stratified sample of 6,233 4 th -grade students covering every city and coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 39 publications
1
22
1
Order By: Relevance
“…Exposure to multiple types of violence and victimization has immediate and lifelong effects on physical and mental health [28][29][30]. Previous research showed that poly-victimization represents a substantial source of higher mental health risk than exposure to any individual victimization type, even when it repeatedly occurs [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to multiple types of violence and victimization has immediate and lifelong effects on physical and mental health [28][29][30]. Previous research showed that poly-victimization represents a substantial source of higher mental health risk than exposure to any individual victimization type, even when it repeatedly occurs [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Chan reported the lifetime adolescent poly-victimization rates in China as 14–18% (Chan, 2014; Chan et al, 2017). A representative study in Taiwan reported that 30% of children aged 10–11 years had experienced four or more types of victimization in the preceding year (Feng et al, 2019). This is comparable to the fact that preceding-year experiences of poly-victimization were reported to be 10% among U.S. children and adolescents aged 2–17 years (Finkelhor et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…40 Abarca et al 41 also found that children with increased number of ACEs, which included maternal physical IPV exposure, had increased adjusted incidence rate ratios for lifetime and current asthma (eg, 4 or more ACEs: incidence rate ratio, 1.81; 95% CI, 1.20-2.71). In a nationally representative cross-sectional study with fourth-grade students in Taiwan, Feng et al 42 reported that children's polyvictimization exposures, to include witnessing interparental violence, had significant dose-response relationship to asthma after adjusting for multiple other family risk factors such as alcoholism or drug abuse (AOR, 1.08; 95% CI, 1.03-1.13, P = .002). A total of 27.8% reported interparental violence.…”
Section: Parental Intimate Partner Violence and Childhood Asthma Inci...mentioning
confidence: 99%